Causal Relationship Between Sex Hormone Binding Globulin and Obstetrical Disorders: A Two-Sample Bidirectional Mendelian Randomization Study - Gan Y; Tan X; Tang Y; Shi Q; Qi H (International Journal of Women's Health, 2025)
Yanqiong Gan,1,2,* Xinlin Tan,2,* Yu Tang,2 Qi Shi,2 Hongbo Qi1 1Department of Obstetrics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Obstetrics, The Affiliated Hospital of North Sichuan Medical College, Nanchong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongbo Qi, Department of Obstetrics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China, Email qihongbo728@163.comIntroduction: Obstetrical disorders critically impact maternal and fetal health. Sex hormone-binding globulin (SHBG) regulates pregnancy maintenance and maternal-infant outcomes through hormonal, metabolic, and inflammatory pathways, yet causal relationships with obstetrical disorders remain unclear. This Mendelian randomization (MR) study examined SHBG’s causal effects on 12 obstetrical conditions.Methods: Using cis-protein quantitative trait loci (cis-pQTLs) of SHBG as instrumental variables, we conducted MR analyses in FinnGen and UK Biobank (UKBB), followed by meta-analyses. Inverse variance weighting (IVW) was primary method, with sensitivity analyses ensuring robustness.Results: IVW-MR demonstrated reduced risks with elevated SHBG: gestational diabetes (OR[95%]=0.835[0.785– 0.889], PFDR=2.03× 10− 7), hyperemesis gravidarum (OR[95%]=0.823[0.728– 0.931], PFDR=5.94× 10− 3), gestational hypertension (OR[95%]=0.917[0.852– 0.987], PFDR=0.041), and early-pregnancy hemorrhage (OR[95%]=0.853[0.794– 0.916], PFDR=6.90× 10− 5). Meta-analysis confirmed SHBG’s causal role in gestational diabetes (P_combined< 0.05). COLOC revealed shared loci between SHBG and five disorders: gestational diabetes, hyperemesis, early hemorrhage, preterm delivery, and postpartum hemorrhage.Conclusion: SHBG causally lowers risks of gestational diabetes, hypertension, hyperemesis, miscarriage, and preterm delivery, highlighting its clinical relevance in obstetrical pathophysiology.Keywords: sex hormone binding globulin, obstetrical disorders, Mendelian randomization